The Effect of Liquidity Ratio, Leverage Ratio, and Cash Flow on Financial Distress - Suhari Suhari (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2025)
This study examines the effect of liquidity, leverage, cash flow, and managerial agency cost on financial distress among manufacturing companies listed on the Indonesia Stock Exchange. Using multiple linear regression analysis, the results show that liquidity and cash flow have a significant negative effect on financial distress, indicating that firms with higher current ratios and stronger operating cash flows are less likely to experience financial difficulties. In contrast, leverage and managerial agency costs have a significant positive effect, suggesting that excessive debt and inefficient managerial spending increase the likelihood of financial distress. The coefficient of determination (R²) of 0.983 indicates that these four variables explain 98.3% of the variation in financial distress. The findings emphasize the importance of maintaining financial efficiency and controlling agency costs to enhance corporate financial stability.